Implementation of the ATIK Model in Animated Drawing Learning for Early Childhood at TK Al Azhar 13 Rawamangun - Tri Rahayu Budiarti; Sri Watini (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
ATIK is a learning approach that emphasizes learning through observation, imitation and application. This concept is often used in arts and crafts education, but can also be applied in a variety of other learning contexts. The purpose of this study is to examine the effect of the ATIK model program based on Animated Drawing Application in improving children's drawing skills, especially in making animated drawings. The type of research used is a case study. The research subjects were 25 children. Data collection techniques used interviews, observation, and documentation. The results showed that the use of the ATIK model with the Aminated Drawing application has a variety of benefits in improving learning in various educational contexts. This is evidenced by the results of children's ability to draw developing rapidly, technology integration can increase children's creativity, stimulate collaboration, share ideas and inspiration through digital media.